Intentional paronymy in the Russian linguoculture - Михайленко-Зото, Олена Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The purpose of this study is to identify and systematize speech-behavioral situations (SBS) and speech-cultural scripts (scenarios) (SCS) of intentional paronymy, which traditionally include paronomasia and paronymic attraction, in the Russian linguocultural space. The object of study is paronyms used intentionally in various speech-behavioral situations of the Russian linguocultural space. The subject of the research is the originality of the system of speech-behavioral situations and the speech-cultural scripts caused by them provided that paronymy is intentionally used. The facts were investigated based on the Russian paronyms dictionaries. As a result of the work carried out, it was possible to show that in situations of intentional paronymy, two types of speech-behavioral tactics (SBT) can be used: the tactics of intentional paronymic replacement / substitution / error and the tactics of artistic design of speech. The author’s conclusions are as follows: firstly, speech-behavioral situations of the intentional use of paronymy arising in the tactics of intentional paronymic substitution / error are a slip of the tongue, a misspelling, a mishearing, a misreading with possible speech-cultural scenarios of jokes, satire, irony, humorous or comic overtones, as well as overtones of condemnation, resentment, humiliation, ridicule, adventure, deception and others. In this case, only the wrong component of the paronymic opposition organized according to the principle of the „right” // „wrong” dichotomy is used. An exception is the mishearing situation, where both components of the paronymic pair are represented. Secondly, speech-behavioral situations arising in the tactics of artistic design of speech using paronymy are patronymic convergence and paronymic rhyming. These two speech-behavioral situations are accompanied by a speech-cultural script of enhancing the artistry and / or expressiveness of the text and the SCS of described assessment. In speech-behavioral situations of patronymic convergence and paronymic rhyming, at least two components of the paronymic series are represented, since intentional paronymy appears in these situations as a binary stylistic device.